The effect of laser welding modes on mechanical properties and microstructure of 304L stainless steel parts fabricated by laser-foil-printing additive manufacturing - Hung, Chia-Hung; Chen, Wei-Ting; Sehhat, M. Hossein; Leu, Ming C. (International journal of advanced manufacturing technology, 2021)
The success of laser-foil-printing (LFP) additive manufacturing depends critically on the laser welding of sheet metals onto the substrate or the previous layer during the part fabrication process. The welding can be generally categorized into two modes: conduction mode and keyhole mode. In this study, 304L stainless steel parts fabricated by the LFP process using the two laser welding modes are compared. The porosity, microstructure, and tensile properties of the fabricated parts in these two modes are measured and compared in the laser scanning direction ( X ) and part building direction ( Z ). The parts fabricated in the conduction mode have a higher density than those fabricated in the keyhole mode. On the tensile properties, both yield strength (YS) and ultimate tensile strength (UTS) have insignificant differences statistically based on the ANOVA analysis between the tensile specimens fabricated with the two welding modes by the LFP process. However, the conduction-mode parts have higher elongation than the keyhole-mode parts in both the X and Z directions, and the difference is especially significant in the Z direction. By using the electron backscattered diffraction (EBSD), it was found that the much higher ductility for the conduction-mode parts in the Z -axis direction is mainly due to the distinct grain boundary interface density in the Z -axis direction between the two welding modes.